An Evaluation of Minority and Female Performance in Army Rotary Wing Aviation Training. Volume II Evaluation Report. Research Report 1319 - Brown, William R.; Army Research Inst. for the Behavioral and Social Sciences, Alexandria, VA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
An evaluation was conducted of minority (Black, Hispanic, Asian, American Indian) and female performance in the Army's Initial Entry Rotary Wing flight training program. Each minority group was compared to a matched sample of majority students. The groups were matched on several test scores, education level, age, rank, and source of entry. The performance of the two groups (each minority and its matched control group) was compared on the following criteria: (1) warrant officer candidate military development course (WOCMDC) grades, (2) academic grades by phase of training, (3) flight performance grades by phase of training, (4) overall grade, (5) attrition during the warrant officer development course, and (6) attrition during the flight portion of training. No significant differences were found in performance grades during WOCMDC. The only group found to have a significant difference in academic grade was the Black group during the primary stage of training; the academic grade average for Blacks was significantly lower. There were no significant differences in flight performance grades or in overall program grade. The Hispanic group was the only group to show significantly more recycles (i.e., repetition of a stage of training) than their matched majority group. During flight training, only Blacks and Hispanics had significantly more recycles than did their matched majority groups. The results of this study will be used by the Army Aviation Center to ensure that the flight training program maximizes the training for all students. (Author/KC)
ERIC Note: Volume I, the Executive Summary, is not available from ERIC.
Educational level discussed: Postsecondary Education.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; American Indians; Asian Americans; Blacks; Females; Flight Training; Grades (Scholastic); Hispanic Americans; Military Personnel; Military Service; Military Training; Minority Groups; Outcomes of Education; Postsecondary Education; Program Effectiveness; Program Improvement; Student Attrition; Army; Reports, Evaluative; Numerical/Quantitative Data